Micro-remediation Experiments of Acid Sulphate Soils - Bakri; Imanudin, Momon Sodik; Hermawan, Agus; Afifah, Della Abelya (Journal of Smart Agriculture and Environmental Technology, 2023)
Soils that are acid sulfuric have low productivity, because the physical and biological conditions of this land are characterized by high acidity. Based on the problem of acid sulphate soil, micro remediation research is carried out to fulfill objectives such as the formation of good and sustainable cultivation land. Acid sulphate soil was taken from at Mesuji Ogan Komering Ilir in January 2023. The method in this study was field observation by taking samples using a belgi drill at several points of the land. The study used a pot with a size of 12 cm x 15 cm which was washed 5 times to remove the acid content in the soil. The pot contains 40% soil, 40% sugarcane husk and 20% rice husk biochar. The object used in this study is the ginger plant. High levels of soil acidity can trigger the dissolution of toxic elements and increase the cause of nutrient deficiencies. Adsorption of complexes in the soil will offer sufficient nutrients for plant development if the soil is rich in soluble bases. Conversely, the soil will tend toward acid if Al and H dominate the adsorption complex. The results of this study can be concluded that micro remediation using sugarcane pulp and biochar has a very real impact. The use of sugarcane bag and biochar in this study helped reduce the initial Al of 9.97 Cmol+/kg to 1.65 Cmol+/kg in the soil and lowered the soil acidity level in the initial soil with a pH of 3.26 to a soil pH of 4.94.